Comparative study for activation of hydorgen peroxide by chemical reagents (Fe2+, Al3+) to reduce chemical oxygen demand in petrochemical wastewater - Bala, M.S.; Abdul Aziz, Mohd Azoddein; Ahdash, M.I.; Alshwal, B.Y. (Malaysian Technical Universities Network (MTUN), 2018)
Environmental pollution by toxic compounds is gaining wider concern in modern developed society. The petroleum refining industry produces a large amount of wastewater due to the amount of water used in refining the processes, particularly for cooling systems and lead to increasing wastewater that will impact the environment. The aim of this research is to reduce chemical oxygen demand (COD) in petrochemical wastewater by activation of hydrogen peroxide using two different reagents (Fe2+, Al3+). In this research was compared several parameters to COD removals such as the effects of concentration / dosage of H2O2, concentration, and dosages of Al2(SO4)3 and concentration and dosages of FeSO4 on the removal efficiency of COD. In this study is proven the effect of Fenton’s reagent process besides the dosage between hydrogen peroxide (H2O2) and ferrous ion (Fe2+) in the reagent that Fenton process was highly efficient to decrease COD and total suspended solid (TSS) reduction. However, addition of aluminium with hydrogen peroxide does not have any effect to remove COD. The result found that overall removal was achieved by 70% in term of COD, and 88 % in term of TSS using Fenton’s reagent process.